Conceptions and Misconceptions of Adult Education in Contemporary Tanzania - Kanukisya, Blackson (Papers in Education and Development, 2021)
The purpose of this paper is to study conceptions and misconceptions of adult education and their sources in Tanzanian context and to suggest a common framework for conceiving adult education which is acceptable both in research and in the conventional usage of the term. Methodologically, the paper uses desk research. The study found misconceptions of adult education among Tanzanians and their respective sources. The study further unveils that the definition of adult education hinges on three aspects: the purpose and utility of adult education; the providers of adult education; and the duration and formality of adult education. The study recommends for improving clarity and sensitization of the concept of adult and adult education in Tanzania. Keywords: adult, adult education, categorization definition, philosophy of adult education